Influence of pregravid preparation on the structural reorganization of the endometrium in women with chronic endometritis in infertility - Daria V. Smirnova; Aleksei M. Gerasimov; Lyudmila V. Kulida; Tatyana V. Verteletskaya; Anna I. Malyshkina (IP Berlin A.V., 2022)
Aim. To reveal the peculiarities of structural reorganization of the endometrium in various variants of pregravid preparation in women with chronic endometritis (CE) and infertility. Materials and methods. We examined 90 women aged 1840 who were treated for CE. For all patients, examination with microbiological (cultural) examination of the cervical canal to be separated for aerobic and facultative anaerobic microorganisms with the determination of sensitivity to antibiotics, ultrasound examination (ultrasound) of the pelvic organs and morphological examination of endometrial biopsy samples before and after treatment. All women of the study group were divided into 2 subgroups. Patients of the 1st subgroup (n=30) received standard treatment for CE antibacterial and non-steroidal anti-inflammatory drugs; in the 2nd (n=60) an additional course of immunostimulating therapy with a bacterial lipopolysaccharide preparation was prescribed. Results. According to the cultural method, repeated cultures from the cervical canal after treatment turned out to be sterile more often in women of the 2nd subgroup. Ultrasound diffuse-focal changes in the subendometrial zone of the myometrium occurred in all patients before and after treatment. In the 2nd subgroup, after treatment, significant changes in the endometrium were noted in the form of an increase in its thickness and a 4-fold decrease in the number of hyperechoic inclusions in the basal layer, as well as the disappearance of the irregularity of the endometrial closure line. In the endometrial biopsies of women of the 2nd subgroup, a significant decrease in the specific area of the inflammatory infiltrate, the absence of foci of fibrosis, and an increase in the thickness of the vessel wall were noted. Conclusion. The addition of a bacterial lipopolysaccharide to the standard CE treatment regimen not only improves the microbiological environment of the female genital tract, but also significantly affects the morphofunctional state of the endometrium.